2021
DOI: 10.3390/en14092391
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Abrasive and Impact Wear Due to Multi-Shaped Particles in a Centrifugal Pump via CFD-DEM Coupling Method

Abstract: Since solid particles suspended in the fluid can cause wear in centrifugal pumps, intensive attention has been focused on the numerical prediction for the wear of flow parts in centrifugal pumps. However, most numerical studies have focused on only one wear model and a sphere particle model. The impact of particle shape on the wear of flow parts in centrifugal pumps is under-studied, particularly considering abrasive and impact wear simultaneously. In this work, the Computational Fluid Dynamics (CFD)-Discrete … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 15 publications
(17 reference statements)
0
9
0
Order By: Relevance
“… C n and C t are normal and tangential recovery coefficients, depending mainly on particle properties. 42…”
Section: Mathematical Modelmentioning
confidence: 99%
“… C n and C t are normal and tangential recovery coefficients, depending mainly on particle properties. 42…”
Section: Mathematical Modelmentioning
confidence: 99%
“…Tang et al (Tang et al, 2021) investigated the effect of particle shape on the wear properties of centrifugal pumps with CFD-DEM. The results show that as the sphericity of the particles increases, the overall pump impact wear first decreases and then increases.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the particle transport in the diffuser was nonuniform, the particle transport in the diffuser was in unit of strands, and the particle transport in the pump was in pulse mode, and the particle transport characteristics in the latter stage were similar to those in the previous stage. Tang et al [22] considered the movement characteristics of particles and simulated the solid-liquid flow in a single-channel pump by CFD-DEM coupling method. The results showed that the smaller the particles, the wider the velocity distribution range and peak value; the larger the particle, the greater the contact force.…”
Section: Introductionmentioning
confidence: 99%